In vitro gas production assessment of concentrate diet containing ginger rhizome meal at varying levels (2009)
Ginger rhizome is a spice and may be beneficial in ruminant nutrition due to its inherent anti-microbial factors. Being an emerging additive, in vitro assessment may be necessary to evaluate its nutritive value. Thus, varying levels of ginger rhizome as dietary inclusion was examined. Dried ginger rhizome was ground into powder and added to a concentrate diet at 0, 50, 100, 150 and 200g/kg. The diet samples were incubated using in vitro gas production technique. Gas production was measured at 3, 6, 9, 12, 15, 18, 21 and 24 h post incubation to estimate total gas volume, methane (CH4), metabolisable energy (ME; MJ/kg DM), organic matter digestibility (OMD; %) and short chain fatty acids (SCFA; µmol/200 mg DM)) were estimated using 4mL of 10M NaOH. Dynamics of gas production characteristics over time were described by equation y = a + b (t-e). DM was similar across all the treatments. The CP ranged between 14.98% for 150g of ginger/kg and 18.13% for 200g/Kg ginger supplementation. The total volume of gas produced by the diets consistently increased from the control diet to 150g/Kg ginger inclusion and thereafter declined significantly (p<0.05). The values ranged from 5.20 to 6.42 for ME, 39.19 to 46.08for OMD and 0.43 to 0.65 for SCFA. However, the CH4 production varied from 8.00 mL to 10.00 mL with no significant difference. The highest level of methane production was obtained in the 50g/Kg ginger inclusion level. The result showed that the ginger inclusion in the diet enhanced the availability of nutrients resulting in higher digestible and metabolisable energy with reduced methane production.